The Social Organization of Personal Support Work in Long-Term Care and the Promotion of Physical Activity for Residents: An Institutional Ethnography - Benjamin, Kathleen Mary Bertha (Université d'Ottawa / University of Ottawa, 2011)
Despite the benefits of physical activity for older adults, many residents living in long-term care homes (LTC) are relatively inactive. Previous research has revealed barriers to physical activity at the resident-level, organizational, and environmental level. However, little attention has been paid to other factors influencing physical activity within the broader institutional complex. The goal of this study was to uncover how the work of personal support workers (PSWs) related to the promotion of physical activity was socially organized. Institutional Ethnography (IE), developed by Dorothy Smith, guided this study. Smith proposed that peoples’ everyday experiences in local settings are organized, often unknowingly, by the actions of people located outside of the local setting and that this organization is textually-mediated. Two LTC homes in Ontario participated in this study. I began data collection by observing PSWs as they went about their work. Next, I interviewed PSWs and other people located inside (e.g. nurses, managers) and outside the LTC homes (e.g. representatives from the Ministry of Health and Long-Term Care (MOHLTC). Lastly, I collected texts that organized the PSWs’ work, such as Ministry standards. The findings revealed that although the MOHLTC standards were viewed as producing something “good” for the residents, some of the standards disrupted the PSWs’ work, which made it challenging for them to support daily physical activity. The promotion of physical activity was seen as an additional program that happened a few times per week and it was parceled out as a professional activity that was socially organized “out” of the PSW role. The findings suggest that local solutions are needed. A good starting point would be to go and talk to PSWs and residents to determine what type of assignments would permit the incorporation of physical activity into daily care. To embed the promotion of physical activity into daily care, a major rethink and reorganization of PSWs work will be needed, including a greater investment in human and material supports for PSWs.
Keywords: physical activity; seniors; long-term care; nursing homes; personal support workers; Institutional Ethnography